Propuesta de la aplicación de la filosofía Lean construction en fiscalización de proyectos de construcción en la ciudad de Guayaquil. Caso de estudio proyecto de El Morro, provincia del Guayas durante el periodo 2021 - Zambrano García, Silvana Martha (2024)
Innovation is currently sought in project management. The objective of this research is to propose the use of tools from the Lean Construction philosophy. Through the inductive evaluation of a works inspection project and carrying out surveys and interviews with professionals who carry out the inspection, administration and execution of works to know their perception, and identify the critical points and thereby improve the inspection processes. and control in the management of civil works.......